2012
DOI: 10.1371/journal.pone.0041045
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Whole Genome Analysis of Human Papillomavirus Type 16 E1-1374∧63nt Variants

Abstract: Background The variation of the most common Human papillomavirus (HPV) type found in cervical cancer, the HPV16, has been extensively investigated in almost all viral genes. The E1 gene variation, however, has been rarely studied. The main objective of the present investigation was to analyze the variability of the E6 and E1 genes, focusing on the recently identified E1-1374 ∧ 63nt variant. Methodology/Principal Findings Variation within the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 64 publications
4
21
1
Order By: Relevance
“…The duplication of 63 nucleotides (E1‐1374^63nt duplication] was first reported by Dong et al [], who investigated HPV16 positive cervical cancer cases in the Chinese Population. This intragenic duplication was also recently described in Croatia and Slovenia [Sabol et al, , ; Bogovac et al, ]. However, previous reports demonstrated that the E1‐1374^63nt duplication was linked with the European variant and was associated preferentially with low‐grade cervical intra‐epithelial neoplasia cases [Sabol et al, , ; Bogovac et al, ].…”
Section: Introductionsupporting
confidence: 70%
“…The duplication of 63 nucleotides (E1‐1374^63nt duplication] was first reported by Dong et al [], who investigated HPV16 positive cervical cancer cases in the Chinese Population. This intragenic duplication was also recently described in Croatia and Slovenia [Sabol et al, , ; Bogovac et al, ]. However, previous reports demonstrated that the E1‐1374^63nt duplication was linked with the European variant and was associated preferentially with low‐grade cervical intra‐epithelial neoplasia cases [Sabol et al, , ; Bogovac et al, ].…”
Section: Introductionsupporting
confidence: 70%
“…Each monomer is indicated by a different color and the center of this structure is where DNA is pulled apart by β-hairpin processes. This figure is adapted from (Sabol, Matovina, Si-Mohamed, & Grce, 2012) and https://www.intechopen.com/books/the-mechanisms-of-dnareplication/replicative-helicases-as-the-central-organizing-motor-proteins-in-themolecular-machines-of-the-elon…”
Section: E1mentioning
confidence: 99%
“…Most oncogenic or high-risk (HR) types associated with invasive cervical cancer (Li et al, 2011; Munoz et al, 2003; Smith et al, 2007) are clustered in one clade of the alpha-HPVs that contains species groups alpha-5, alpha-6, alpha-7 and alpha-9 (Burk et al, 2009; Schiffman et al, 2005) and account for ∼90% of all cervical cancers worldwide (Li et al, 2011; Smith et al, 2007). Despite phylogenetic relatedness, HPV variants can differ in pathogenicity (Berumen et al, 2001; Burk et al, 2003; Chan et al, 2013; Cornet et al, 2013b; Giannoudis and Herrington, 2001; Hecht et al, 1995; Sabol et al, 2012; Schiffman et al, 2010; Villa et al, 2000; Xi et al, 2007). Because of their medical importance, the predominant research focus on papillomaviruses is their association with pathologic and oncogenic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison between all sequences identified a total of 540 single nucleotide polymorphisms (SNPs) with any pair of sequences having a maximum of 180 (2.3% of genome) differences. In addition to these genomes, Sabol et al (2012) have reported a 63 bp duplication within the E1 ORF (HPV16 (E1).1374_1436dup, also listed as E1-1374^63nt duplication) and 76 complete HPV16 genomes were sequenced from central China (Sun et al, 2012), although the heterogeneity was limited to the A lineages. The most striking observation about HPV16 variants is the presence of genetic heterogeneity in what is called the “non-European” lineages (i.e., lineages B/C/D) in contrast to the relative homogeneity of the A (European) lineage.…”
Section: Introductionmentioning
confidence: 99%